Chronic cutaneous lupus erythematosus with systemic symptoms or systemic lupus erythematosus? - Suresh K. Malhotra (Nasza Dermatologia Online, 2016)
Chronic cutaneous lupus erythmatosus (CCLE) and Systemic lupus erythematosus(SLE) are two separate diseases with some overlapping features. Upto 28% patients with CCLE are susceptible to develop SLE. But in some cases patients may present with CCLE with systemic features without developing SLE. Here, we present a case of Chronic cutaneous lupus erythematosus with systemic symptoms simulating SLE with no positive immunological markers to support the diagnosis of SLE.